Rancang Bangun Tongkat Pintar Berbasis Internet Of Things (IoT) Bagi Penyandang Tunanetra - Puspitasari, Rahayu; Diamah, Aodah; Maruddani, Baso (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2024)
This study designed and tested an Internet of Things (IoT)-based smart cane for the visually impaired. The research method used Research and Development (Borg & Gall) with a prototype that combines ESP32, ultrasonic sensors, water level sensors, and gyroscopes. IoT integration was carried out through a Telegram bot for sensor reading notifications and GPS coordinate transmission. Functional testing showed that object detection in front was effective at a distance of <100 cm and puddle detection successfully activated audible alerts and notifications. Network testing showed varying notification delays between locations, so local audible alerts were used as the primary safety route, while Telegram served as a supporting tool. In conclusion, the prototype functioned well for obstacle detection, puddle detection, and location tracking, and is worthy of further development by optimizing sensor placement and connectivity. It produced an average latency and delay of <150 seconds with a jitter of 1–75 seconds. Overall results indicate that the prototype functions well and has the potential to become a reliable IoT-based navigation aid for the visually impaired.